Intergovernmental Fiscal Systems and Development Aid : Comparisons and Lessons of Experience - Adugna, Abebe; Ford, J. Fitz (World Bank, Washington, DC, 2017)
This paper reviews the experiences of intergovernmental fiscal systems (IGFS) to look for possible lessons for how Official Development Assistance (ODA) is delivered. Specifically, it compares IGFS and ODA in two specific respects. The first is the proportion of public resources that central governments make available to sub-national governments on a conditional basis, and how that compares with the proportion of non-earmarked ODA given to low income countries. The second is the role of performance outcome in resource allocation to sub-national governments and how that compares with the role of performance in ODA, particularly multilateral ODA allocation. The comparisons show that: (i) the share of earmarked ODA is more than three times higher than that of conditional grants in intergovernmental systems, suggesting that donors in ODA rely more on earmarking to influence the spending decisions of the recipient countries than their federal governments do on conditional grants to induce policy changes in their own sub-national governments; and (ii) none of the OECD countries currently use outcome measures in determining resource allocation to their sub-national governments for a variety of good reasons, and the recent debate as to whether multilateral ODA allocation should be based on development outcomes seems to ignore this experience.